B-Type Natriuretic Peptide as Prognostic Marker in Newly Diagnosed Acute Coronary Syndrome Patients - Shila, Jakia Sultana; Begum, Shirin Akter; Khan, Md Aminul Haque; Begum, Noortaj; Rahman, Md Matiur; Parvin, Dilshad (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: B-type Natriuretic Peptide (BNP) a neurohormone synthesized in ventricular myocardium and released into the circulation in response to ventricular dilatation and pressure overload, is a current biomarker used for identifying patients at high risk of Acute Coronary Syndrome (ACS). High level of BNP is associated with an increased risk of Major Adverse Cardiac Events (MACE) including new or progressive heart failure and myocardial infarction. The objective of this study was to assess the prognosis of newly diagnosed ACS patients by using plasma BNP level. Methods: This study was conducted in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) in collaboration with National Institute of Cardiovascular Disease (NICVD) from January 2013 to December 2013. Total 100 newly diagnosed ACS patients, aged 30 to 70 years, irrespective of sex who reported within 24 hours of onset of symptoms were enrolled in this study by purposive and convenient sampling. Plasma BNP level of selected study subjects was measured within 24 hours of onset of symptoms. Then subjects were grouped on the basis of their empirical cut-off value of plasma BNP concentration Group I having plasma BNP level <135 pg/mL and Group II having plasma BNP level 135 pg/mL. Results: Of 100 ACS patients, 86 were male and 14 were female with the mean age 49.61±10.28 years and the age range of 30 to 70 years. Among 26 patients in Group I, good recovery, morbidity and mortality were 22 (84.6%), 4 (15.4%) and zero and among 74 patients in Group II good recovery, morbidity and mortality were 18 (24.3%), 53 (71.6%) and 3 (3.0%) respectively. Differences in outcome between groups were statistically significant (P=0.001). Above the empirical cut-off value of BNP (135 pg/mL) good prognosis was for 18 (24.3%) and bad prognosis was for 56 (75.7 %) patients and relative risk 3.48 in 95% CI (2.25-5.36). Conclusion: It can be concluded from this study that higher baseline plasma BNP concentration is associated with more adverse clinical outcomes in ACS patients. Since the baseline plasma BNP concentrations at the onset of event shows incremental prognostic value, so plasma BNP can be used clinically as a biomarker of prognosis in ACS patients. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22870 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 1-5